The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1959
DOI: 10.1172/jci103948
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Exchange of Sodium Between Plasma and Cerebrospinal Fluid*†

Abstract: This study is concerned with the mechanism of exchange of sodium between plasma and cerebrospinal fluid (CSF). Several workers (1, 2) have reported that there is no significant difference between the concentration of sodium in plasma and CSF. reported that the average concentration of sodium in CSF, in man, exceeded the plasma concentration by about four mEq. Davson (4) has determined the distribution ratio of sodium between CSF and plasma as 0.975 in the dog, correcting for the difference in water content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1961
1961
1992
1992

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…The resistance of the acidic response to 10 % (v/v) C02 agrees with the barrier resistance to trypan blue (Clemedson, Hartelius & Holmberg, 1958), to 24Na (Fishman, 1959), and to albumin (Lending et al 1961). …”
Section: Hc03-+h+ -H2co3 -H20+ T C02supporting
confidence: 70%
“…The resistance of the acidic response to 10 % (v/v) C02 agrees with the barrier resistance to trypan blue (Clemedson, Hartelius & Holmberg, 1958), to 24Na (Fishman, 1959), and to albumin (Lending et al 1961). …”
Section: Hc03-+h+ -H2co3 -H20+ T C02supporting
confidence: 70%
“…Intravenous injection of AVP enhanced sodium transport into the cerebrospinal fluid (CSF) and lowered CSF production. 1 -2 Intraventricular injection of AVP increased transport of labeled water from blood to brain, enhanced water movement across the arachnoid villi, increased brain water content, aggravated cold-injury edema, and increased ependymal permeability but did not alter CSF production. 3 -7 In an earlier study we showed that the intracerebral injection of AVP caused an increase in brain water content that could be inhibited by an antagonist to the V, receptor of vasopressin.…”
Section: T He Neuropeptides Arginine Vasopressin (Avp)mentioning
confidence: 99%
“…The gall bladder is another example in which sodium is pumped from epithelial cells into intercellular channels, which are distended when sodium transport is acceler¬ ated and collapsed when sodium transport is inhibited (Tormey & Diamond, 1967). Fishman (1959) also obtained experimental evidence suggesting that the choroid plexusses were a target for the action of ADH in enhancing the exchange of sodium between plasma and CSF. Leusen & Lacroix (1961) found that the intraventricular infusion of hypotonie saline had a diuretic effect, perhaps because the decrease of sodium concentration in the CSF reduced or stopped the release of ADH from the neural lobe.…”
Section: Antidiuretic Hormone In Csf and Osmoreceptorsmentioning
confidence: 99%